Corneal Endothelial Characteristics, Central Corneal Thickness, and Intraocular Pressure in a Population of Chinese Age-Related Cataract Patients - Yingmei Li; Zhentao Fu; Jian Liu; Miao Li; Yuguang Zhang; Xinyi Wu (Journal of Ophthalmology)
Purpose. To describe corneal endothelial characteristics, central corneal thickness, and intraocular pressure in a population of Chinese age-related cataract patients and to determine the effects of age, gender, hypertension, and body mass index (BMI). Methods. 1551 eyes were examined preoperatively. The parameters measured were endothelial cell density (CD), average cell area (CA), coefficient of variation (CV), cell hexagonality (HEX), central corneal thickness (CCT), intraocular pressure (IOP), and axial length (AL). Results. There were significant differences in CV and BMI between genders. There was a significant decrease in CD, CCT, and IOP and, conversely, an increase in CA and BMI with increasing age. The patients who suffered from hypertension had bigger CA, less CD, and lower HEX than the patients who did not suffer from hypertension. CD has a negative correlation with age and CV and a positive correlation with CCT, CCT has a positive association with CD and IOP, and IOP had a negative relationship with age and a positive relationship with CCT, CA, and HEX. Conclusions. Normative data for the corneal endothelium, central corneal thickness, and intraocular pressure in the normal age-related cataract patients are reported which will serve as a baseline for comparative studies about cataract.